Time pressure drives impulsive buying behavior through hedonic motivation and utilitarian motivation: An e-commerce perspective - Farah Salsabila; Fatchur Rohman; Raditha Dwi Vata Hapsari (Jurnal Fokus Manajemen Bisnis, 2025)
People's consumption habits and other aspects of daily life have changed due to the internet's quick development. The COVID-19 pandemic accelerated the adoption of digital platforms, especially e-commerce, but recently, performance has declined on some major platforms, such as Tokopedia. To maintain competitiveness, innovative marketing strategies such as live streaming features through time pressure encourage impulsive buying behavior. This research examines how time pressure affects impulsive buying behavior, considering hedonic and utilitarian motivations as factors that mediate this relationship. The study was motivated by conflicting results from earlier research about how time pressure influences impulsive buying behavior, along with the rising popularity of online shopping via live streams among Generation Z. A quantitative approach was employed using a structured online questionnaire distributed to 170 respondents in Malang, Indonesia, who had purchased fashion products via live streaming in the past three months. Data were analyzed using Structural Equation Modelling with Smart Partial Least Square to evaluate relationships among variables. The findings showed that time pressure significantly and positively influences impulsive buying behavior and hedonic and utilitarian motivation. Both hedonic and utilitarian motivations were also found to positively affect impulsive buying behavior and significantly mediate the relationship between time pressure and impulsive buying behavior. These findings highlight that emotional and rational motivations are crucial in shaping impulsive buying behavior under time pressure in the live streaming environment. The research contributes to understanding consumer behavior in digital commerce and provides practical implications for e-commerce marketers seeking to optimize live-streaming strategies to stimulate impulse buying.